Estimation of Variance and Heritability Components in F2 Populations of Maize (Zea mays L.) in Dry Land - Amanah Aulia Adeputri; M. Taufik Fauzi; Suwardji; A. A. Ketut Sudharmawan (Jurnal Biologi Tropis, 2023)
The F2 population of maize plants that has been obtained from hybridization between NK212 and NK7328 varieties has not been suspected of genetic diversity components and heritability in the narrow sense. This study aimed to determine the magnitude of the alleged value of variety components and heritability, as well as determine the types of varieties to be formed. The experimental design used was the Group Randomized Design (RAK) - North Carrolina I (NCI) consisting of 120 treatments. The experimental setup involved 40 male parent plants, each paired with 3 female parent plants in season I, and this procedure was replicated twice, resulting in a total of 240 treatment groups. The collected data was subjected to analysis through variety analysis (ANOVA) utilizing the NCI model. The results showed that the presumptive value of additive variety and dominant variety based on the results of data analysis varied, but in all observed traits the dominant variety value tended to be greater. Most of the observed traits have a negative heritability presumptive value, except for stem diameter, panicle exit age, fresh pruning weight, and 1000 seed weights. The conclusion obtained is that most of the observed properties have additive variance values and negative heritability values; the dominant variance value in all observed properties is greater than that of additive variety; The heritability of most traits cannot be predicted because they are negative. Therefore, it is advisable for the improvement of the F2 population is with the formation of hybrids.